Osteolipoma in posterior maxilla: A case report - Anbinder, Ana Lia; Milhan, Noala Vicensoto Moreira; Trocino, Benjamín Sánchez; Taylor, Adalberto Mosqueda (Journal of Oral Diagnosis, 2017)
Osteolipoma is a histologic variant of lipoma characterized by bone formation, which rarely occurs in the oral cavity. This condition usually is easily recognized by microscopic examination and it has a good prognosis. However, this lesion may occur in different sites of the oral cavity and may present different clinical aspects, being a diagnostic challenge at the time of clinical examination. The aims of this article are to report a case of osteo- lipoma located in the buccal aspect of the posterior maxilla and discuss the main clinical and histological findings of this rare oral lesion. A 46-year-old woman presented with a painless mass of about 2 cm in the vestibular portion of the posterior maxilla. The lesion had a hard consistency and color similar to adjacent mucosa. Imaging findings revealed a well-defined and circumscribed hypodense lesion with hyperdense areas. The histopa- thological examination showed mature adipose tissue among trabeculae of vital lamellar bone, which was consistent with the diagnosis of osteolipoma. No signs of recurrence were observed after 3 years of follow-up.